Radiotherapy-induced mesorectum alterations: histological evaluation of 90 consecutive cases. (February 2014) - Reggiani Bonetti, Luca; Domati, Federica; Farinetti, Alberto; Migaldi, Mario; Manenti, Antonio
Abstract Objective. In order to identify the radiotherapy-induced histological modifications in the mesorectum, we reviewed the surgical specimens of 90 rectal resections comprehensive of the total mesorectal excision (23 cases radiologically classified as cT2N0M0 and 67 as cT3N0M0). All patients were preoperative treated with radiotherapy: 20 with 50 Gy, 20 with 20 Gy and 50 Gy irradiation associated to FOLFOX scheme chemotherapy. Material and methods. Routine hematoxylin and eosin stained serial slides at 5 mm of intervals were obtained from surgical specimens and included the tumor site and the adjacent irradiated mucosa, the submucosa and the muscular layers of the rectal wall and the mesorectal adipose tissue, completely removed until to the mesorectal fascia. Ten subjects (eight cT2N0M0 and two cT3N0M0), who did not received preoperative oncological treatments were adopted as controls. Results. Histologically, examination revealed fibrosis of the adipose tissue in 86 cases (95%), vascular damage including vasculities and fibrotic thickening wall of arteries and veins in 46 cases (51%), sclero-hyalinosis of lymph nodes with pericapsular fibrosis in 22 cases (23%) and perineural deposition of fibrosis in 12 (13%). These findings were ubiquitously observed in the whole mesorectum. Fibrosis of the adipose tissue and vasculitis were mainly associated to the combination of 50 Gy radiations plus chemotherapy (p < 0.05). Conclusion. The detection of histopathological alterations in the mesorectum can give reason of the well-known postoperative complications and long-term sequels.